RESTRICTED CANCELLATION AND WEAKLY RESTRICTED CANCELLATION FUZZY MODULES - Yahya Khalaf, Dr.Hatam (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, we introduce and study (restricted cancellation, weakly restricted cancellation) fuzzy modules as generalization of notions restricted cancellation (weakly restricted cancellation) modules. We give many basic properties about both concepts.